Proposed wax refinery - Angeles, Anita; Nable, Marita; Pagaduan, Patrocinio (Diliman, Quezon City College of Engineering, 1963)
This project involves thd esign of a wax refinery using propane as solvent. The following results were obtained : for a capacity of 4,000,000 pounds of paraffin wax which is 1/3 the present demand based on importations for 1961.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Chemical plants; Waxes industry; Propane